2023
DOI: 10.3390/vaccines11040776
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Influenza and Other Airborne Transmission Viruses during the 2021/2022 Season in Hospitalized Subjects in Tuscany, Italy

Abstract: Winter in the northern hemisphere is characterized by the circulation of influenza viruses, which cause seasonal epidemics, generally from October to April. Each influenza season has its own pattern, which differs from one year to the next in terms of the first influenza case notification, the period of highest incidence, and the predominant influenza virus subtypes. After the total absence of influenza viruses in the 2020/2021 season, cases of influenza were again recorded in the 2021/2022 season, although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Fourteen [32,38,40,41,44,46,48,51,53,58,6166] out of 29 full-length articles were judged at low risk of bias, while the remaining 15 studies [30,33–37,42,49,50,52,5456,59,60,6466] had at least one possible source of bias (S5 Table). The most frequent criticalities concerned insufficient description of patients and setting, inappropriate sample frame and small sample size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen [32,38,40,41,44,46,48,51,53,58,6166] out of 29 full-length articles were judged at low risk of bias, while the remaining 15 studies [30,33–37,42,49,50,52,5456,59,60,6466] had at least one possible source of bias (S5 Table). The most frequent criticalities concerned insufficient description of patients and setting, inappropriate sample frame and small sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported data on viral co-detections [30,31,36,37,40,47,51,53,54,[60][61][62][63]. However, only five estimates [37,47,51,53,63] were based on a sufficient (≥30) number of RSV-positive samples and were therefore less prone to the small study effect (S11 Table ).…”
Section: Prevalence Of Viral Co-detectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies reported data on viral co-detections [30,31,36,37,40,47,51,53,54,[60][61][62][63]. However, only five estimates [37,47,51,53,63] were based on a sufficient (�30) number of RSV-positive samples and were therefore less prone to the small study effect (S11 Table ).…”
Section: Prevalence Of Viral Co-detectionsmentioning
confidence: 99%
“…Out-of-season samples were frequent (38%; 13/34) and most studies analyzed only (56%; 19/34) upper respiratory tract specimens. The majority (74%; 26/35) of studies were funded by public institutions.Fourteen[32,38,40,41,44,46, 48,51,53,58,[61][62][63][64][65][66] out of 29 full-length articles were judged at low risk of bias, while the remaining 15 studies [30,33-37, 42, 49, 50, 52, 54-56, 59, 60, 64-66] had at least one possible source of bias (S5 Table). The most frequent criticalities concerned insufficient description of patients and setting, inappropriate sample frame and small sample size.…”
mentioning
confidence: 99%